2021
DOI: 10.3390/ijerph18168796
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of COVID-19 Pandemic Lockdown on the Physical Performance of Professional Soccer Players: An Example of German and Polish Leagues

Abstract: The purpose of this study was to investigate whether the in-season pandemic lockdown influenced physical match performance in professional soccer players who participated in the competition of German Bundesliga and Polish Ekstraklasa. The data from 306 games for German Bundesliga and 296 games for Polish Ekstraklasa were divided into before- and after-lockdown periods. The physical performance of German Bundesliga teams after the 63-day COVID-19 lockdown did not differ significantly from that in the first part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 35 publications
3
22
0
2
Order By: Relevance
“…Many questions remain about how the virus affects the bodies of athletes, and emerging data regarding this issue can help us to paint a clearer picture of how to deal with the infection as efficiently as possible and to return the athlete to his or her regular training regimen with minimal risks to the athlete’s health. Previous studies have mainly focused on the performance of athletes after a quarantine period (lockdown) [ 13 , 14 ]. A study of the physical performance in the top German and Polish national soccer (football) leagues showed that after the quarantine period, there was a significant decline in both high-intensity running and distance covered per game in Polish league matches, while in Germany, no significant differences were found [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many questions remain about how the virus affects the bodies of athletes, and emerging data regarding this issue can help us to paint a clearer picture of how to deal with the infection as efficiently as possible and to return the athlete to his or her regular training regimen with minimal risks to the athlete’s health. Previous studies have mainly focused on the performance of athletes after a quarantine period (lockdown) [ 13 , 14 ]. A study of the physical performance in the top German and Polish national soccer (football) leagues showed that after the quarantine period, there was a significant decline in both high-intensity running and distance covered per game in Polish league matches, while in Germany, no significant differences were found [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have mainly focused on the performance of athletes after a quarantine period (lockdown) [ 13 , 14 ]. A study of the physical performance in the top German and Polish national soccer (football) leagues showed that after the quarantine period, there was a significant decline in both high-intensity running and distance covered per game in Polish league matches, while in Germany, no significant differences were found [ 14 ]. A similar study was conducted on a sample of matches in the highest soccer league in Spain, and significantly higher running variables values were observed in the pre-COVID period, while on the other hand, increased values of accelerations/min and decelerations/min were noted in the post-COVID period [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although many hypotheses have been proposed regarding the possible negative impacts the COVID-19 lockdown will have had on the physical performance of players once competition is restarted [3,4,21], recent studies have provided inconsistent findings. In brief, Radzimi ński et al recently reported that the physical performance in German Bundesliga was not affected by the COVID-19 lockdown, while on the other hand, Polish Ekstraklasa matches after the COVID-19 lockdown had a significantly shorter total and high-intensity running distance [22]. García-Aliaga et al compared the MRPs before and after the COVID-19 lockdown in Spain and found lower medium-speed running (14.1-21 km/h), high-speed running (21.1-24 km/h), and sprinting distances (>24 km/h) in matches after the COVID-19 lockdown.…”
Section: Introductionmentioning
confidence: 99%
“…García-Aliaga et al compared the MRPs before and after the COVID-19 lockdown in Spain and found lower medium-speed running (14.1-21 km/h), high-speed running (21.1-24 km/h), and sprinting distances (>24 km/h) in matches after the COVID-19 lockdown. The authors suggested that such a difference could have been caused by different break lengths and different restrictions implemented in these countries during the pandemic lockdown [22].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has had a disrupting effect on global society, including the suspension of league games, and various sports events (Radzimiński et al, 2021 ; Schumacher et al, 2021 ), such as the 2020 Tokyo Olympics and the 2020 European Cup football (Grazioli et al, 2020 ). After 2 months of confinement, the German national football association recommended players to perform home-based training programs, followed by small-group training sessions (Meyer et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%